Investigation and Research into Chinese Translation Errors in the names of dishes in Thai Cuisine: This study focuses on the menu of the restaurants in Siam Square business district as an example - Zhu, Guangde; Numtong, Kanokporn (Journal of China-ASEAN Studies, 2023)
There are more and more cultural studies on the names of cuisines in academia, but few studies have focused on the Chinese translations of Thai cuisines precisely, and the study of their translation errors is still a new field. Under the guidance of translation theory, the survey samples are analysed item by item, taking into account the characteristics of Chinese and Thai cuisine names, categorising the problems of lexical errors, grammatical errors and aesthetic errors, and suggesting that the causes of translation errors include the non-equivalence of language, secondary translation errors, over-reliance on machine translation and lack of professionals. translation suggestions were puts forward from three aspects: vocabulary, grammar and aesthetics. On the basis of these suggestions, it should be beneficial to suggest that government authorities provide regulation and support to the cuisine industry, the education circle cultivates more Chinese language professionals, the cuisine community strengthens Chinese language training, the AI translation software optimises its system, and consumers correct errors intentionally